PEMURNIAN VIRGIN COCONUT OIL MENGGUNAKAN ZEOLIT 3A SEBAGAI BAHAN BAKU OBAT KULIT - Suharmadi, Sri Handayani; Enjarlis, Enjarlis (Universitas Negeri Semarang, 2016)
Virgin coconut oil (VCO) is the feedstock for the production of cocozone oil, a substance that can be used as a medicine for several skin problems. This work is aimed to find the best method for producing VCO with low water content which is the prerequisite to be a suitable feedstock of cocozone oil. Two methods of VCO production i.e. agitation in room temperature (30oC) and cooling at 5oC for 24 hours were compared. The amount of zeolite 3A added to 20 ml of VCO was varied on 10, 20, and 30 gram. It is found that the agitation method with 30 gram zeolite 3A can lower the water content down to 30%.